PEMBELAJARAN BAHASA INGGRIS SECARA DARING MELALUI YOUTUBE - Yefta Christian; Robin Robin; Moh Fariq Aziz; Rara Tri Kencana; Ricky Rickena Exendy; Ronny Triputra; Santo Tjiam; Tina Rani; Utari Afnesia (National Conference for Community Service Project (NaCosPro), 2020)
English subjects have become part of the established curriculum. Especially for Junior High School and Senior High School levels in Batam City, English is useful as one of the soft skills needed today. However, the problem that arises is that not all students can use English well and fluently. The program offered for this problem is online learning. Students can study independently with materials that can upload via Youtube. The results obtained were students responded well to the materials uploaded on Youtube, so that they could improve their English skills.